2010
DOI: 10.1128/mcb.01372-09
|View full text |Cite
|
Sign up to set email alerts
|

Multiple E2F-Induced MicroRNAs Prevent Replicative Stress in Response to Mitogenic Signaling

Abstract: Transcription of microRNAs (miRNAs) is thought to be regulated similarly to that of protein-coding genes. However, how miRNAs are regulated during the cell division cycle is not well understood. We have analyzed the transcription profiles of miRNAs in response to mitogenic stimulation in primary fibroblasts. About 33% of the miRNAs expressed in these cells are induced upon exit from quiescence. Many of these miRNAs are specifically induced by E2F1 or E2F3 during the G 1 /S transition and are repressed in E2F1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 75 publications
6
88
1
Order By: Relevance
“…It was shown previously that E2F1 activates AKT via transcriptional regulation of the adaptor Gab2 and that this E2F1-dependent AKT activation serves to inhibit E2F1-mediated apoptosis (44). In addition, a recent study showed that in murine fibroblasts, E2F1 and E2F3 transcriptionally upregulate the expression of a number of miRNAs, which can, in turn, inhibit cell proliferation (45).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown previously that E2F1 activates AKT via transcriptional regulation of the adaptor Gab2 and that this E2F1-dependent AKT activation serves to inhibit E2F1-mediated apoptosis (44). In addition, a recent study showed that in murine fibroblasts, E2F1 and E2F3 transcriptionally upregulate the expression of a number of miRNAs, which can, in turn, inhibit cell proliferation (45).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] E2F1 and E2F2 are known to function both as transcriptional activators and as repressors of their target genes, including those coding for microRNAs. [11][12][13][14][15] Moreover, E2F1 and E2F2 perform positive as well as negative regulatory roles in cellular proliferation, which appear to be cell specific and context dependent. They have been reported to promote cellcycle entry and progression upon their ectopic expression.…”
mentioning
confidence: 99%
“…miRNAs are short ncRNAs (~22 nucleotides long) that serve as guides for targeting the RNA to imperfectly complementary miRNA recognition elements (MREs) within target mRNAs inducing both translational repression, and mRNA decapping/deadenylation [4]. Several studies have shown that miRNAs can control the expression levels of genes involved in the cell-cycle regulatory machinery [5,6]. The let-7 miRNA was initially discovered in Caenorhabditis elegans [7], and has been shown to be highly evolutionarily conserved [8].…”
Section: Introductionmentioning
confidence: 99%